The Validity of the Single-Leg Heel Raise Test in People With Multiple Sclerosis: A Cross-Sectional Study - Mañago, Mark M.; Kline, Paul W.; Harris-Love, Michael O.; Christiansen, Cory L. (Frontiers in Neurology, 2021)
Background: The single-leg heel raise test is a common clinical assessment, however, little is known about its validity in people with multiple sclerosis (MS). This study investigated the validity of the single-leg heel raise test in people with MS and a healthy control group (CTL). Materials and Methods: Twenty-one people with MS (49 ±12 years, Expanded Disability Status Scale 1.5-5.5) and 10 healthy controls (48 ±12 years) performed the single-leg heel raise test, ankle plantarflexion strength assessment (electromechanical dynamometry), and mobility measures (Timed 25-Foot Walk, 2-Minute Walk Test, Functional Stair Test). Results: Convergent validity between the heel raise test and strength was moderate for participants with MS completing <20 heel raises (r=0.63, p=0.001) but weak for the entire sample (r=0.30, p=0.020). Compared to the average CTL group values, the heel raise test differentiated between groups on the MS groups’ weaker (p<0.001) and stronger (p=0.003) limbs, while strength only differentiated between groups on the weaker limb (p=0.010). Considering the weaker and strong limbs from the MS group and the CTL group average values, the mobility measures had moderate-to-strong correlations with the heel raise test on the weaker MS limb + CTL (r=0.71-0.78) and stronger MS limb + CTL (r=0.62-0.70), and weak-to-moderate correlations with strength on the weaker MS limb + CTL (r=0.49-0.58, p=0.001-0.007). Discussion: In people with MS, the single-leg heel raise test may be clinically useful as it identified impaired muscle performance, differentiated muscle performance from a control group, and together with the control group, correlated with functional mobility.